METODE PERMAINAN EDUKATIF DALAM PEMBELAJARAN BAHASA ARAB - Nasruni Nasruni (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2017)
AbstractGames of Language or Educative Games are the way of learning Arabic through Games. Game of language is not just as additional activity to having fun, but it can be classified as the way in teaching wich is have the aim to give the learner the opportunity to apply their  language skills. In the process of teaching language, educational games are performed in various forms, one of that  is based on purpose. Educative games are very usefull in recovery, inauguration, and enrichment activities in learning. Besides that, the reality proves that most learners are still weak and have the problem in speaking, writing, and listening skill. These weakness can be overcome gradually by a well designed of the Games . If language teaching does not take a good steps to overcome these weaknesses, learners will always find it difficult to learn the language.Keywords: Implementation, Educative Games, Learning Arabic AbstrakPermainan bahasa atau permainan edukatif merupakan cara mempelajari bahasa Arab melalui permainan. Permainan bahasa bukan merupakan aktivitas tambahan untuk bergembira semata, tetapi dapat digolongkan dalam pengajaran yang bertujuan memberikan kesempatan ke pada peserta didik untuk mengaplikasikan kemahiran bahasa yang telah dipelajari. Dalam pengajaran bahasa, permainan edukatif  dilakukan dalam berbagai bentuk, salah satunya berdasarkan tujuan. Permainan edukatif sangat berguna bagi aktivitas pemulihan, pengukuhan, dan pengayaan dalam pembelajaran. Selain itu, kenyataan menunjukkan bahwa kebanyakan peserta didik masih lemah dalam menghadapi masalah komunikasi, menulis, dan mendengar. Kelemahan ini dapat diatasi sedikit demi sedikit melalui aktivitas permainan yang dirancang dengan baik dan benar. Jika pengajaran bahasa tidak mengambil langkah yang baik untuk mengatasi kelemahan ini maka peserta didik selamanya menemui kesulitan dalam belajar bahasa. Kata kunci : Penerapan, Permainan Edukatif, Pembelajaran Bahasa Arab